2017
DOI: 10.5935/abc.20170135
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prediction of Obstructive Coronary Artery Disease in Patients Undergoing Primary Heart Valve Surgery

Abstract: BackgroundThe prevalence of coronary artery disease (CAD) in valvular patients is similar to that of the general population, with the usual association with traditional risk factors. Nevertheless, the search for obstructive CAD is more aggressive in the preoperative period of patients with valvular heart disease, resulting in the indication of invasive coronary angiography (ICA) to almost all adult patients, because it is believed that coronary artery bypass surgery should be associated with valve replacement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
3
8
0
2
Order By: Relevance
“…However, in younger patients (<50 years) prevalence was much lower (3.3%). 209 These data are similar to those observed in another study that included 3736 patients (mean age, 43.7 years), in which prevalence of obstructive CAD combined with valvular heart disease was 3.42%. 207…”
Section: Complications and Associated Diseasessupporting
confidence: 89%
See 1 more Smart Citation
“…However, in younger patients (<50 years) prevalence was much lower (3.3%). 209 These data are similar to those observed in another study that included 3736 patients (mean age, 43.7 years), in which prevalence of obstructive CAD combined with valvular heart disease was 3.42%. 207…”
Section: Complications and Associated Diseasessupporting
confidence: 89%
“…Entretanto, nos mais jovens (<50 anos), a prevalência foi mais baixa (3,3%). 209 Esses dados são similares aos observados em outro estudo que incluiu 3.736 pacientes (idade média de 43,7 anos), nos quais a prevalência de DAC obstrutiva combinada com doença valvar do coração foi 3,42%. 207 Utilização e Custo da Atenção à Saúde…”
Section: Associação Entre Doença Valvar Do Coração E Doença Arterial ...unclassified
“…Entretanto, em pacientes mais jovens (<50 anos), a prevalência foi mais baixa (3,3%). 217 Esses dados são similares aos observados em outro estudo que incluiu 3.736 pacientes (idade média, 43,7 anos), nos quais a prevalência de DAC obstrutiva combinada com doença valvar do coração foi 3,42%. 191,203 determinantes genéticos e imunes da resposta às infecções estreptocócicas que leva a DCR, 229 preditores clínicos e relacionados a procedimento de eventos de curto e longo prazo após comissurotomia mitral percutânea, 211,230 além de um registro nacional de TAVI.…”
Section: Mortalidadeunclassified
“…Obstructive coronary artery disease in patients of valvular heart disease has been reported to vary from 9%-41% in different studies. [8][9]19 In a recent large study involving 1308 patients by Anthony Matta and Nicolas Moussallemin Lebanese population has reported an overall prevalence for concurrent obstructive CAD of 27.75% in their patients who underwent heart valve surgery. 20 In Pakistan studies by Shaikh et al 21 and Gul et al 22 has reported overall prevalence of obstructive CAD of 31% respectively in their population cohorts.…”
Section: Discussionmentioning
confidence: 99%